Tone orthography and literacy the voice of evidence in ten Niger-Congo languages - Roberts, David, 1959-; Walter, Stephen (Studies in written language and literacy,, 2021)
"This book presents the results of a series of literacy experiments in ten Niger-Congo languages, representing four language families and spanning five countries. It tests the hypothesis, "To what extent does full tone marking contribute to oral reading fluency, comprehension and writing accuracy, and does that contribution vary from language to language?". One of the main findings is that the ethno-literacy profile of the language community and the social profile of the individual are stronger predictors of reading and writing performance than are the linguistic and orthographic profiles of the language. Our data also suggests that full tone marking may be more beneficial for less educated readers and those with less experience of L1 literacy. The book will bring practical help to linguists and literacy specialists in Africa and beyond who are helping to develop orthographies for tone languages. It will also be of interest to cognitive psychologists exploring the reading process, and researchers investigating writing systems"--